2015
DOI: 10.1039/c4gc01759e
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of softwood kraft lignin with dimethyl carbonate

Abstract: Methylation of lignin is essential for inducing thermal stability when a multitude of thermoplastic applications are envisaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 53 publications
1
109
0
Order By: Relevance
“…While lignin is increasingly used for production of thermoplastics, 47 crosslinkers 48 and carbon materials; 49 its use as an aromatic commodity chemical feedstock is minimal with the exception of vanillin production. The present study represents a clear example of how DMC as a reactive co-solvent can be used to intercept reactive intermediates generated during the reductive disassembly of lignin to give aromatic monomers.…”
Section: Discussionmentioning
confidence: 99%
“…While lignin is increasingly used for production of thermoplastics, 47 crosslinkers 48 and carbon materials; 49 its use as an aromatic commodity chemical feedstock is minimal with the exception of vanillin production. The present study represents a clear example of how DMC as a reactive co-solvent can be used to intercept reactive intermediates generated during the reductive disassembly of lignin to give aromatic monomers.…”
Section: Discussionmentioning
confidence: 99%
“…1 With a content of [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] wt%, lignin is a main component of biomass such as wood and annual plants. The total lignin resources on earth are estimated to be 300 billion tons, with a natural production of 20 billion tons per year.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that one of the main constraint on lignin from readily becoming a versatile feedstock for a variety of applications is its heterogeneity which leads to unpredictable and uncontrollable reactions 4,27,28,33 . Consequently, we have examined this issue here by making sure that the PDI of our samples is actually narrow so that we minimize this variable before proceeding to a more complex polydisperse system.…”
Section: Resultsmentioning
confidence: 99%
“…This is a novel approach for the simultaneous systematic modulation of the functionality and the reactivity of lignin developed in earlier parts of our work 7,27 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation